Association of Chest X- ray findings with SARS-CoV-2 severity - Santosh Kumar Sidhwani, Syed Ali Raza, Fatima Zaina, Ali Abbas, Omer Ahmed Shaikh, Sadia Manan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The COVID-19 first surfaced when cluster of pneumonia patients arose in Wuhan, Hubei Province, China. Although the current gold standard for COVID-19 diagnosis is reverse transcriptase-polymerase chain reaction (RT-PCR), chest x-ray (CXR) and computed tomography (CT) play a vital role in sickness diagnosis due to their limited sensitivity and availability. Aim: To evaluate retrospectively the role of CXR, the main radiological findings in it and its diagnostic accuracy in COVID-19 pneumonia. Methods: This is a cross sectional study involving 264 PCR positive COVID-19 patients with their clinical–epidemiological findings admitted at Ziauddin Hospital from May-July 2020. CXRs were taken as digital radiographs in our emergency department’s isolation wards using the same portable X-ray device, according to local norms. CXRs were taken in two directions: antero-posterior (AP) and postero-anterior (PA). The hospitals’ database had all of the images. To determine the number of radiological findings, multiple radiologists on duty completed an independent and retrospective examination of each CXR. In the event of disagreement, a mutual agreement was reached. SPSS version 20 was used for statistical analysis. Results: We were able to find 264 patients who met our criteria. With a mean age of 56.4214.89, the majority of individuals were determined to be males 189(71.6%) and females 75(28.4%). (Range of 16 to 87 years). 127 patients (48.1%) had severe illness symptoms and were admitted to the ICU, while the remaining 102(38.6%) had mild to moderate disease 35(13.3%). Diffuse (29.2%) and middle and lower co-existing distribution (25.8%) whereas just lower lobe (13.3%) were the most common predominance in severity. Peripheral involvement was also seen in (8.7%) cases. Conclusion: Both lungs are equally affected with the disease having the consolidation and opacifications while the effusion is the major complication in the severe cases. Diffuse involvement of the lung lobes is seen in the study followed by the middle and lower lobe involvement. Keywords: X-ray, COVID-19, pneumonia, lungs, consolidation, opacification